1989
DOI: 10.1177/153944928900900603
|View full text |Cite
|
Sign up to set email alerts
|

Program Evaluations of Occupational Therapy Level II Fieldwork Environments: A Naturalistic Inquiry

Abstract: Three occupational therapy Level IIfieidwork environments-mental health, adultphysical disabilities, andpediatrics-were evaluated with the naturalistic inquiry methodology. Students and supervisors described and compared and contrasted ideal clinical education environments with actual Level IIfieldwork environments. The naturalistic inquiry methodology and the salient factors in each of the three evaluated environments are summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Therefore, if the nebulousness of practice within such settings has tended to create problems, special attention needs to be paid to the way these placements are structured so as to give students a more tangible sense of accomplishment. This finding is similar to the Meyers (1989) study, in which her participants identified structure and supervision as being the key factors for an ideal environment in the psychosocial area so as to deal with 'some of the ambiguities of mental health practice' (p359). In addition, students and therapists need to become more explicit about what is and is not being accomplished.…”
Section: Technical-rational Focussupporting
confidence: 79%
“…Therefore, if the nebulousness of practice within such settings has tended to create problems, special attention needs to be paid to the way these placements are structured so as to give students a more tangible sense of accomplishment. This finding is similar to the Meyers (1989) study, in which her participants identified structure and supervision as being the key factors for an ideal environment in the psychosocial area so as to deal with 'some of the ambiguities of mental health practice' (p359). In addition, students and therapists need to become more explicit about what is and is not being accomplished.…”
Section: Technical-rational Focussupporting
confidence: 79%
“…Studies which have been done fall into six main categories: the fieldwork process (Tompson & Tompson, 1987); the effect of fieldwork on students (Christie, Joyce, & Moeller, 1985a); the therapist as clinical educator (Jarski, Kulig & Olson, 1990); student evaluation (Taylor, 1993); costeffectiveness of fieldwork (Shalik, 1987); and students' perspectives of fieldwork (Meyers, 1989). In recent years the increased demand for fieldwork placements has prompted more attention to be paid to this component of the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational therapy researchers have used a range of qualitative methodologies to explore views of health service recipients (Kibele & Llorens, 1989;Kielhofner, 1981) and providers (Fondillen Rosage, & Neuhaus, 1990;Meyers, 1989). To explore therapists' perspectives of their practice for adults with an intellectual disability, qualitative methodology-namely, focus groups-was used.…”
mentioning
confidence: 99%